Validation of Hadlock's and Shepard Formulae of Fetal Weight Estimation in Eastern Region of Nepal - Khadka, Roshana (Birat Journal of Health Sciences, 2019)
Introduction: Ultrasonography plays a pivotal role in present day obstetrics. It has been well recognized that the fetuses of extremes of the normal birth weight range are associated with increased perinatal morbidity, mortality and adverse development outcomes. Categorization of fetal weight into either the small or large for gestational age may lead to timed obstetric interventions that collectively represent significant departure from routine antenatal care. Objective: To compare the accuracy of Hadlock's 1, 2, 3, 4 and Shepard model in estimating expected fetal weight and its comparison with actual birth weight in our population at eastern region of Nepal. Methodology A prospective observational study was performed in the Department of Radiodiagnosis, Nobel Medical college and teaching hospital, Biratnagar, over a period of 6 months dated Jan 2018 to June 2018 using systematic random sampling with sample size estimated as 160, with 5% level of significance, 80% power of test and a maximum of 200 grams differences by our predicting model from actual mean weight. Singleton, term pregnancy (37- 42 weeks gestational age) verified with antenatal USG performed prior to 20 weeks' gestation. Pregnancies complicated by congenital anomalies and deliveries after 2 days of USG examination were excluded. Results: 159 pregnant ladies were enrolled in our study with mean age of 27.60 ± 5.633 years (range 18-43 years). The average (actual) birth weight recorded was 3450.79±438.73gms. The different formulae for estimating birth weight gave us similar results. Estimation of fetal weight by Shepard gave us a mean of 3340.80 ± 463.72. Hadlock1, Hadlock2, Hadlock3 and Hadlock4were 3546.55±429.92grams, 3491.18±439.49 grams, 3445.23 ±422.79grams, and 3446.12±418.43grams respectively. Conclusion: All four Hadlock formulae gave comparable results for fetal weight estimation including the Shepard formula; however, Shepard formula tends to underestimate fetal weight as compared to rest of the formulae. Among the Hadlock's, Hadlock 2 seems to show betier accuracy in fetal weight prediction in our population of study. The mean birth weight recorded using Hadlock 1 formula gave the beer correlation with the actual birth weight though the difference between four Hadlock formulae was all insignificant.